PERLINDUNGAN HUKUM TENAGA MEDIS DAN TENAGA KESEHATAN MELALUI MAJELIS YANG DIBENTUK MENTERI KESEHATAN PASCA UNDANG-UNDANG KESEHATAN OMNIBUS LAW - Vidi Galenso Syarief (Collegium Studiosum Journal, 2023)
The rapid development of life in the health sector has resulted in the need for broader regulations, from medical law to matters related to health (health law) in order to provide legal protection for medical personnel and health workers. The research method used is normative juridical. The results of the study show that legal protection for medical personnel and health workers is contained in the Omnibus Law on Health, one of which is regulated in Article 310 which reads: the consequences of the error are resolved first through alternative dispute resolution outside the court. This article regulates the settlement of losses due to medical or health actions that must be resolved through non-litigation channels first. In addition, the legal protection for medical personnel and health workers in the Health Omnibus Law is regulated in Article 273 paragraph (1), Article 306 paragraph (3), Article 273 paragraph (2), Article 393 paragraph (1) and Article 193. In addition, to provide legal protection for medical personnel, the Minister of Health is preparing to form a special assembly to uphold the doctor's code of ethics as stipulated in Article 304 of the Omnibus Law on Health. This assembly is to maintain the doctor's code of ethics, regardless of the professional organization, the type of doctor and the specialist. With the existence of this assembly, all criminal cases that might ensnare doctors will go to this assembly, before entering the realm of law.